(untitled) (Altre Modernità, 2019)
In their contributions, scholars of different legal disciplines illustrate the difficulties that women victims of violence face in order to obtain acknowledgement and due protection from the competent authorities. Although often concerning specific territorial contexts Ð such as, for instance, Latin America Ð the situations here analysed rather seem different faces of the same coin, due to the deep discrimination against women that characterises them, in an environment still marred by male chauvinism and sexism.